32.1: Invited Paper: Fast‐Phase Full HD Color‐Sequential LCoS‐SLM for Holographic Display Application. (26th August 2021) - Ho, Kung-Chu; Tsai, Chun-Wei; Wang, Chen; Lee, Tse
Abstract : We have developed a new full HD fast‐phase LCoS spatial light modulator (SLM) with color‐sequential function. Combining the optimization of liquid crystal materials with our digital driving technology, the response time can be achieved to less than 10 msec, which is expected suitable to be applied on the head‐up display (HUD) and other holographic fields. This result will increase the potential of LCoS‐SLM be used for the color holographic display in the future automotive market.